How to better promote teaching? Unveiling the links between Professional Learning Communities and Intrinsic Motivation among Foreign Language Teachers - Chunxiu Long; Chili Li; Guangfang Huang; Jingyin Fu (Heliyon, 2024)
Professional Learning Communities (PLCs) assume a vital role in promoting teacher growth and development, while the presence of intrinsic motivation (IM) in the work environment profoundly impacts teacher performance. Unveiling the interconnections between teachers' engagement in PLCs and their intrinsic motivation holds the potential to enhance the overall well-being of both teachers and students. This study used a mixed-methods approach to investigate the relationship between PLCs and IM of Chinese Teachers of Foreign Languages (CTFL) in higher education. The questionnaire survey and semi-structured interviews were conducted among 198 teachers in 19 provinces of China. The quantitative data were analyzed by means of descriptive analysis and regression analyses with SPSS 22.0 and the qualitative data were processed by following thematic analysis. Results demonstrated that the participants' perceptions on their PLCs and IM were at a moderately high level, with mean scores at 3.56 and 3.86 on a 5-point Likert scale, respectively. Regression analyses revealed a significant positive correlation between PLCs and IM. Specifically, Shared Vision (SV), Supportive Environment (SE) and Collaborative Learning (CL) in PLCs were positively correlated with Willingness to Take on Challenges (WTC) and Love for Work (LW) in IM. The qualitative findings highlighted the significance of supportive environment and teacher's work engagement in affecting teacher's perceptions on PLCs. Job Characteristic of foreign language teacher, along with significant others might also influenced teachers' intrinsic motivation. Implications for PLCs leadership and foreign language teachers are discussed.